The Cellulase Enzyme Activity of Thermophilic Bacteria from Way Belerang Hot Spring, Lampung - Rismawati Hidayah; Erma Suryanti; Meezan Ardhanu Asagabaldan; Budhi Agung Prasetyo (Universitas Labuhanbatu, 2025)
Background: The demand for cellulase enzymes across various industries continues to rise, while most of the current supply still depends on imports. Therefore, exploring local biological resources, such as thermophilic bacteria capable of producing cellulase, is crucial. This study aims to isolate and evaluate the cellulase enzyme activity of thermophilic bacteria from the Way Belerang Hot Spring in South Lampung, Indonesia. Methodology: The research involved isolating bacteria from hot spring water samples, conducting qualitative and quantitative assays of cellulase activity, and characterizing the isolates. Findings: A total of 24 bacterial isolates were obtained, 16 of which demonstrated cellulolytic activity, as indicated by clear zones on 1% CMC agar. The two most promising isolates, S5.1 and S5.24, exhibited the highest cellulolytic indices of 2.728 and 2.395, respectively. These isolates were further tested quantitatively using a glucose standard curve to determine their enzyme activity. The highest cellulase activity for isolate S5.1 was recorded at the 10th hour with 5.1 × 10⁻² U/mL, while isolate S5.24 showed peak activity at the 14th hour with 3.1 × 10⁻² U/mL. Contribution: This study represents the first investigation of thermophilic amylase-producing bacteria from the Way Belerang Hot Spring, highlighting the potential of thermostable amylase enzymes that can withstand high temperatures for future industrial applications.